Implementation of Lean Manufacturing to Identify and Minimize Waste in The Welding Framebody Department of PT XYZ - Awanis, Anggita; Vikaliana, Resista (Journal of Emerging Supply Chain, Clean Energy, and Process Engineering, 2023)
PT XYZ is a transportation equipment manufacturing company that must always maintain that the products it produces can achieve sales targets. However, in carrying out the production process, PT XYZ often experiences shortages in the production process, one of which is due to problems in the welding frame body department.  Thus, the objectives of this research are to determine the flow of the production process in the welding frame body department, then analyze the waste that occurs in the body parts of the welding frame. This frame body welding department has a production process flow starting from St. Rear Frame 1 to St. Rear Frame 4, then St. Front Frame 1 to St. Front Frame 3, after that St. General Assy, Permanent Robot/Robot Handling, Fine Boring, Manual 1 and Manual 2, and ending in Tapping and Numbering. Based on the flow of the production process, it was found that St. Rear Frame 3 is the most problematic with a percentage of 21%. By using the DMAIC method, in the Define stage, it was found that the most common problem that occurred in St. Rear Frame 3 was a torn pipe in lower jig B with a percentage of 6%. At the Define stage, it is also known that the root cause of the problem is the lack of accuracy from the operator, who may be sleepy at work due to lack of rest, or even chatting, which results in setting teaching too far because it is more dominant to the lower, not to the iron connection between the lower and the subframe. Then, at the measurement stage, the target is to reduce 6% of the problems to 4%. Furthermore, at the analysis stage, an analysis is carried out to determine if the potential problem occurs and then what next steps will be conducted which is useful for minimizing waste. At the Improve and Control stage, namely, the steps taken to minimize the problem or waste (preventive actions) and what steps or ways to do if the problem or waste occurs again (contingent actions).